2021
DOI: 10.1038/s41598-021-98330-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bacterial abundance and communities in the nipple drinking system of cascading cage layer houses

Abstract: Water quality is critical for egg production and animal health in commercial layer housing systems. To investigate microbial contamination in nipple drinking system in layer houses, the bacterial abundance and communities in water pipes and V-troughs on different tiers (e.g., 1st, 3rd, 5th, and 7th tiers) of a layer house with 8 overlapping cage tiers were determined using qRT-PCR and 16S rRNA sequencing. The water bacterial abundance (i.e., genome 16S rDNA copy number, WBCN) in water pipes and V-troughs did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In our results, the abundance of Proteobacteria both in jejunal content and mucosa was negatively associated with the body weight gain. Comamonas, a Gram-negative pathogenic bacterium, can cause degradation of steroid hormones [33,34], is predominately associated with bacteremia [35], and can occasionally cause low virulence diseases in human and animals [36]. A recent study demonstrated that a higher abundance of Acinetobacter markedly increased systemic inflammation via inducing IFN-γ and IL-6 production [37] and resulted in poor efficiency in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
“…In our results, the abundance of Proteobacteria both in jejunal content and mucosa was negatively associated with the body weight gain. Comamonas, a Gram-negative pathogenic bacterium, can cause degradation of steroid hormones [33,34], is predominately associated with bacteremia [35], and can occasionally cause low virulence diseases in human and animals [36]. A recent study demonstrated that a higher abundance of Acinetobacter markedly increased systemic inflammation via inducing IFN-γ and IL-6 production [37] and resulted in poor efficiency in broilers [38].…”
Section: Discussionmentioning
confidence: 99%
“…Acinetobacter is associated with diseases such as septicemia, pulmonary infections, meningitis, and diarrhea in humans and animals, with a mortality rate of about 20–60% [ 68 ]. Comamonas is a Gram-negative pathogenic bacterium that causes steroid hormone degradation [ 69 , 70 ], is primarily associated with bacteremia [ 71 ], and occasionally causes low-virulence disease in humans and animals [ 72 ]. Shigella is a common and potentially pathogenic enteric pathogen that can cause bacterial food poisoning, typhoid fever, and uremia but is also present in small amounts in the feces of healthy individuals [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to quantify through future research the number of the free-range hens that were seen eating simultaneously, and the behavioral evidence of restricted feed access or resource competition. Most of the surveyed farms used nipple systems for providing water, which save water and reduce microorganism contamination [ 60 ]. The drinker space per hen on caged farms ranged from 10 hens/drinker at the lower end to the three hens/drinker at the highest.…”
Section: Discussionmentioning
confidence: 99%